2010
DOI: 10.1111/j.1865-1682.2010.01140.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Routines that Contribute to On-farm Biosecurity as Reported by Swedish Livestock Farmers

Abstract: On-farm biosecurity is important for preventing the spread of several contagious animal diseases. In this study, biosecurity routines among Swedish farmers with livestock (cattle, pigs, sheep or goats) were examined through questionnaires posted by mail. Moreover, the use of protective clothing among professionals visiting farms, such as animal transporters and veterinarians, were investigated through assessments made by the farmers. Questionnaires were completed, partly or fully, by 518 farmers (overall respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
97
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(110 citation statements)
references
References 11 publications
13
97
0
Order By: Relevance
“…From the maps it is clear that the cattle trade is constantly active at quite a high level. Recent studies have concluded that many farms lack sufficient biosecurity routines (Nöremark et al, 2010a), and there is, in other words, a constant risk that contagious diseases can spread in the population. Historically, Sweden has had a relatively low level of infectious diseases in livestock and claim freedom from several serious diseases that are present on the European continent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the maps it is clear that the cattle trade is constantly active at quite a high level. Recent studies have concluded that many farms lack sufficient biosecurity routines (Nöremark et al, 2010a), and there is, in other words, a constant risk that contagious diseases can spread in the population. Historically, Sweden has had a relatively low level of infectious diseases in livestock and claim freedom from several serious diseases that are present on the European continent.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with other countries, Swedish farmers have been spared from major disease outbreaks and there are indications that this has lowered their awareness regarding this type of threat (Nöremark et al, 2009b(Nöremark et al, , 2010a. With modern communication and transports allowing quick and long distance contacts, the introduction of an exotic and highly contagious disease could therefore have massive consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Although the importance and usefulness of biosecurity is elaborately described, studies demonstrated that most cattle farmers do not implement adequate biosecurity measures (Nöremark et al, 2010;Negron et al, 2011;Brennan and Christley, 2012;Sayers et al, 2013). In Belgium, an important cattle and milk producing country in Europe and a very densely populated livestock area, the application of biosecurity measures in pig and poultry herds has already been studied (Ribbens et al, 2008;Van Steenwinkel et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Biosecurity measures are of great importance to prevent or limit the risk of animals becoming infected with pathogens (Amass and Clark, 1999;European Commission, 2007;Maes et al, 2008;Fraile et al, 2010;Nöremark et al, 2010;Lambert et al, 2012;Laanen et al, 2013). A reduction in the risk of contracting an infection might lead to the reduced necessity of (antimicrobial) treatment of the animals (Laanen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%